Long-Term Natural Course of Pathologic Myopia in Chinese Patients. (19th March 2019) - Chen, Minjie; Yu, Manrong; Dai, Jinhui; Chu, Renyuan
Abstract : Purpose . To investigate the natural progression in Chinese patients with pathological myopia (PM) and its associated factors. Methods . The medical records of 28 patients with PM (worse than −6 diopter), including 31 eyes of 21 children and 12 eyes of 7 adults, were studied. All of the patients underwent a complete ophthalmologic examination at least twice over 3-year period, including the measurement of refractive error (shown as spherical equivalent, SE), axial length (AL), intraocular pressure, visual acuity (uncorrected visual acuity, UCVA, and best-corrected visual acuity, BCVA), and dilated fundus examination. Results . The median AL of adults increased significantly from 29.8 mm to 31.43 mm over 5.4 years follow-up (P = 0.0037 ), accompanied with the median SE progressing significantly from −16.4 D to −18.94 D (P = 0.0005 ). Similarly, the median AL of children increased significantly from 26.13 mm to 27.81 mm over 3.9 years (P = 0.0001 ). However, the improvements of UCVA and BCVA in children were significant (P = 0.0304, 0.0001), and they had a negative correlation with age (P = 0.0010, 0.0005). Also, UCVA and BCVA in children with bilateral PM were significantly better than those with unilateral PM (P = 0.0385, 0.0210). Conclusions . Fundus degenerations in children with pathological myopia may lead its way since the age of 10 years. Besides, children with bilateral pathological myopia can have parallel development in visual acuity.